The Indonesian Migrant Workers in The Shackles of Agamben's Biopolitics Point of View - Muhammad Rustamaji; Shalih Mangara Sitompul; Aldi Rizki Khoiruddin; Alarico Mendonca Tilman (Jurnal Hukum, 2025)
The migration of Indonesian workers in search of better economic opportunities is a global phenomenon. However, behind the narratives of remittances and national development lies a grim reality of human rights abuses and systemic exploitation. While various frameworks, such as human rights. This study analyzes the persistent violence against Indonesian Migrant Workers (IMWs) in Malaysia—particularly shootings by the Malaysian Maritime Enforcement Agency—through Giorgio Agamben’s biopolitical framework. It reveals a novel application of Homo Sacer, bare life, and state of exception concepts to show how sovereign power systematically strips undocumented IMWs of political recognition (Bios), reducing them to mere biological existence (Zoe) and legitimizing extrajudicial killings without accountability. This research used normative legal research and deductive reasoning, the findings demonstrate that these acts are not incidental law enforcement excesses but a deliberate biopolitical strategy embedded in Malaysia’s state apparatus. By exposing the legal “grey zone” that enables such dehumanization, this research advances the theoretical link between Agamben’s political philosophy and migrant protection, urging a fundamental rethinking of legal and diplomatic responses to dismantle the biopolitical logic that normalizes violence, exclusion and negates the presumption of innocence. Through Agamben's optic, the shooting of Indonesian Migrant Workers by Malaysian Maritime Enforcement Agency or Royal Malaysia Police is not just a case of ordinary human rights violations, but also a manifestation of how the modern state creates homo sacer.